2013
DOI: 10.1371/journal.pone.0070798
|View full text |Cite
|
Sign up to set email alerts
|

Phenyl 1,2,3-Triazole-Thymidine Ligands Stabilize G-Quadruplex DNA, Inhibit DNA Synthesis and Potentially Reduce Tumor Cell Proliferation over 3′-Azido Deoxythymidine

Abstract: Triazoles are known for their non-toxicity, higher stability and therapeutic activity. Few nucleoside (L1, L2 and L3) and non-nucleoside 1,2,3-triazoles (L4–L14) were synthesised using click chemistry and they were screened for tumor cell cytotoxicity and proliferation. Among these triazole ligands studied, nucleoside ligands exhibited higher potential than non-nucleoside ligands. The nucleoside triazole analogues, 3′-Phenyl-1,2,3- triazole-thymidine (L2) and 3′-4-Chlorophenyl-1,2,3-triazole-thymidine (L3), de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…4). The observed biocompatibility of the 1,2,3‐triazole‐based polymers P1–P8 is in accordance with literature data, stating a nontoxicity of many polytriazole‐containing structures, mainly designed in the pharmaceutical field, for example, as a tool for drug discovery for cancer treatment . Because of its chemical composition, the triazole units are not subject to metabolic degradation and are stable in typical biological conditions, which are usually of aqueous and mildly reducing nature .…”
Section: Introductionsupporting
confidence: 88%
“…4). The observed biocompatibility of the 1,2,3‐triazole‐based polymers P1–P8 is in accordance with literature data, stating a nontoxicity of many polytriazole‐containing structures, mainly designed in the pharmaceutical field, for example, as a tool for drug discovery for cancer treatment . Because of its chemical composition, the triazole units are not subject to metabolic degradation and are stable in typical biological conditions, which are usually of aqueous and mildly reducing nature .…”
Section: Introductionsupporting
confidence: 88%
“…Binds preferentially to MYC G4 x [ 124 ] N,N'-bis(3,4-dihydroxbenzy lidene)-1,2-diaminobenzene (crosslinker) B16F1 m n.a. x [ 131 ] Naphthalene diimide derivatives (compound 2) SKMEL-5 h 48 h IC 50 : 1.7 μM x x [ 132 ] PhenDC3 A375 h 96 h GI 20 : 10 μM x [ 69 ] Phenyl 1,2,3-triazole-thymidine ligands (L1, L2, L3) B16F10 m 24 and 48 h IC 50 : 200 μM (L1), 125 μM (L2), 50 μM (L3) x [ 133 ] PPL3C M14 h 96 h IC 50 : 0.8 μM x [ 128 , 134 ] Pyridostatin A375 h 96 h GI 20 : 1.5 μM x [ 69 ] RHPS4 M14 h , PLF2 h , JR1 h , JR8 h , SBCL1 h , SAN h , LP h , LM h , JR5 h , M14 h 5 and 7 days IC 50 : 3.1 μM (5 days M14), ~1 μM (5 days PLF2 h , JR1, JR8, SBCL1, SAN) ~1 μM (7 days M14, PLF2 h , JR1, JR8, SBCL1, SAN) About 50% reduced tumor growth in melanoma xenografts x [ 135 137 ] ...…”
Section: Introductionmentioning
confidence: 99%
“…6-Substituted furo [2,3-d]pyrimidine derivatives (7 and 8) were prepared by intramolecular in situ O-hereoannulation ring closure of N-1-alkyl-C-5-alkynylpyrimidine derivatives (3 and 5). Copper(I)-catalysed click reaction of 5-iodo-N-1-propargylpyrimidine (2) with corresponding azides followed by Sonogashira cross-coupling reaction with terminal alkynes gave novel 1,4-disubstituted 1,2,3-triazole tethered 5-alkynylpyrimidine (14-19) and 6-substituted furo [2,3-d]pyrimidines (20)(21)(22). In vitro antiproliferative activity of novel compounds evaluated on human cancer cell lines cervix adenocarcinoma (HeLa), colon adenocarcinoma (CaCo-2), chronic myeloid leukemia in blast crisis (K562), Burkitt lymphoma (Raji) revealed that 3,5-difluorophenyl and p-(trifluoromethyl)phenyl substituents in pyrimidine (19) and furo [2,3- …”
Section: Discussionmentioning
confidence: 99%
“…Introduction of alkynyl substituents at C-5 of pyrimidine ring by Sonogashira cross-coupling reaction of 9-13 gave 5-alkynylpyrimidines (14-19) and 6-substituted furo [2,3-d]pyrimidines (20)(21)(22) with 1,2,3-triazole moiety at N-1 and N-3, respectively. 6-Substituted furo [2,3-d]pyrimidines (20)(21)(22) were obtained by in situ 5-endo-dig cyclization of C-5-alkynyl-N-1-(1,2,3-triazolyl) uracil derivatives (16, 17 and 19) using CuI and base (Scheme 2).…”
Section: Chemistrymentioning
confidence: 99%
See 1 more Smart Citation